2018
DOI: 10.1002/elps.201800115
|View full text |Cite
|
Sign up to set email alerts
|

A new method for microwave assisted ethanolic extraction of Mentha rotundifolia bioactive terpenoids

Abstract: A new microwave-assisted extraction (MAE) method using ethanol as solvent has been optimized by means of a Box-Behnken experimental design for the enhanced extraction of bioactive terpenoids from Mentha rotundifolia leaves; 100°C, 5 min, 1.125 g dry sample: 10 mL solvent and a single extraction cycle were selected as optimal conditions. Improved performance of MAE method in terms of extraction yield and/or reproducibility over conventional solid-liquid extraction and ultrasound assisted extraction was also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…bioactives. Whereas the advantages associated with ohmic, microwave or ultrasound-assisted hydrodistillation to obtain essential oils rich in volatile bioactives have been described in a number of studies [13][14][15][16][17], literature regarding the development of procedures based on pressurized liquid extraction (PLE) [18], ultrasound-assisted extraction [19,20] or microwave-assisted extraction (MAE) [21][22][23][24][25] for the enhanced recovery of Mentha sp. bioactives is much more limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…bioactives. Whereas the advantages associated with ohmic, microwave or ultrasound-assisted hydrodistillation to obtain essential oils rich in volatile bioactives have been described in a number of studies [13][14][15][16][17], literature regarding the development of procedures based on pressurized liquid extraction (PLE) [18], ultrasound-assisted extraction [19,20] or microwave-assisted extraction (MAE) [21][22][23][24][25] for the enhanced recovery of Mentha sp. bioactives is much more limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the fact that direct heating of the solvent by microwave irradiation has been shown to improve the speed and efficiency of bioactive extractions and the bioactivity of MAE extracts, previous applications of this advanced technique to Mentha sp. have commonly focused on a single Mentha species (Mentha piperita [21,24,25], M. pulegium [22], M. rotundifolia [23]), making the comparison of this effect difficult. Moreover, no previous study has addressed the optimization of an MAE method to obtain multifunctional extracts from different Mentha species, as the antimicrobial activity of MAE extracts of Mentha sp.…”
Section: Introductionmentioning
confidence: 99%
“…of its essential oils, mainly obtained by distillation or hydrodistillation [5][6][7]. However, studies regarding the composition and bioactivity of extracts from this Mentha species obtained using polar solvents are scarce [8,9]. Moreover, no previous study has addressed the changes with harvesting year for extracts from M. rotundifolia samples collected at the same harvesting stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although solid-liquid extraction (SLE) is the most widely used procedure to obtain bioactive extracts because of their undeniable advantages in terms of simplicity and affordability, advanced extraction techniques such as microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE) and subcritical water extraction (SWE), are gaining importance as efficient alternatives for bioactive extraction [10]. While UAE [11][12][13][14] and MAE [8,11,15] have been previously described to provide improved performance for the extraction of Mentha bioactives, SWE has been scarcely applied for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Kohari et al, (2020) [ 14 ] applied solvent-free microwave extraction to Mentha arvensis L. in order to obtain essential oils and demonstrated that this method is more efficient than traditional hydrodistillation extraction. The fragrance components such as limonene and piperitone were found in a higher amount in microwave extraction compared with the traditional method [ 14 , 15 ]. A microwave-assisted extraction method has been optimized by using ethanol as a solvent to extract terpenoids from Mentha rotundifolia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%